Contrasting melt regime in the Ice Grounding Zone of Thwaites Glacier, West Antarctica - Gadi, Ratnakar; Rignot, Eric; Menemenlis, Dimitris; Scheuchl, Bernd (Proceedings of the National Academy of Sciences - PNAS, 2025)
The contribution of Thwaites Glacier, Antarctica, to sea level rise is influenced by how quickly warm salty seawater of Circumpolar Deep Water origin melts basal ice near its grounding line. Satellite observations reveal tidally forced kilometer-scale seawater intrusions beneath grounded ice that form an "Ice Grounding Zone" (IGZ) where ice melts vigorously. Although melt rates have been measured at selected sites using Automated phase-sensitive Radar Echo Sounders (ApRES) and Automated Underwater Vehicle (AUV) instruments, their spatial distribution and total magnitude within the IGZ remain uncertain. Here, we present 2D high-resolution simulations of the melt regime of Thwaites Glacier using the Massachusetts Institute of Technology global circulation model ocean model. The model predicts high melt at the entrance of the IGZ, with a quadratic decay inside the IGZ, a linear increase with ocean thermal forcing and a sublinear increase with cavity length. On the slow-moving Thwaites Eastern Ice Shelf, the modeled melt rate is low (10 m/y) due to a flat, shallow ice base, in agreement with in situ observations from AUV and ApRES instruments. On the Thwaites Glacier Tongue (TGT), the modeled melt rate is high (50 m/y) due to a steeper and deeper ice base. The modeled melt rates are consistent with the estimates derived from the satellite. Hence, multiple lines of evidence indicate high melt in the IGZ of TGT, which controls 80% of the glacier mass balance. An updated representation of grounding zones in ice sheet models including seawater intrusions will increase their sensitivity to ocean warming and will revise sea-level projections upward.